(untitled) (Global Journal of Science Frontier Research, 2023)
The possibility of experiencing things that may not be attainable in real life, such as going to Mars, swimming with dolphins, or performing with the Rolling Stones, can be realized through the application of Virtual Reality (VR). By utilizing computer graphics and Human-Computer Interaction (HCI), we can create a virtual environment that enables us to interact with almost any conceivable scenario. In short, VR technology enables us to see and experience anything through the power of computergenerated imagery.